2023
DOI: 10.1177/02692163231154760
|View full text |Cite
|
Sign up to set email alerts
|

How is community based ‘out-of-hours’ care provided to patients with advanced illness near the end of life: A systematic review of care provision

Abstract: Background: Deaths in the community are increasing. However, community palliative care out-of-hours is variable. We lack detailed understanding of how care is provided out-of-hours and the associated outcomes. Aim: To review systematically the components, outcomes and economic evaluation of community-based ‘out-of-hours’ care for patients near the end of life and their families. Design: Mixed method systematic narrative review. Narrative synthesis, development and application of a typology to categorise out-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…From 64 papers included in the original review [ 22 ], 31 reported data on use of out-of-hours services from ten different countries ( Table 1 ). 33 provided no information on the use of services, and were therefore excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From 64 papers included in the original review [ 22 ], 31 reported data on use of out-of-hours services from ten different countries ( Table 1 ). 33 provided no information on the use of services, and were therefore excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our original systematic review of models of out-of-hours services [ 22 ] found improved patient outcomes for community out-of- hours services provided 24/7 by specialist palliative care services offering both hands-on clinical care and advisory care. However, resources are limited, notably workforce shortages, meaning that this model is not always feasible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations